Selective in-vitro Enzymes- Inhibitory Activities of Fingerprints Compounds of Salvia Species and Molecular Docking Simulations - ÖZHAN KOCAKAYA, ŞAFAK; ERTAŞ, ABDULSELAM; Yener, Ismail; Ercan, Bahadir; VARHAN ORAL, ELİF; Akdeniz, Mehmet; Kaplaner, Erhan; TOPÇU, GÜLAÇTI; TOPÇU, GÜLAÇTI; Kolak, Ufuk (My University, 2020)
Recently Nutrition and Food Chemistry researches have been focused on plants and their products or their secondary metabolites having anti-alzheimer, anti-cancer, anti-aging, and antioxidant properties. Among these plants Salvia L. (Lamiaceae) species come into prominence with their booster effects due to high antioxidant contents, which have over 900 species in the world and 98 in Turkey. Some Salvia species are already in use as herbal treatment of vessel stiffness, Dementia like problems and cancer. Recently some species of Salvia are of extensive research topic. In this study, inhibitory potentials of secondary metabolites, rosmarinic acid, salvigenin, salvianolic acid A and B, tanshinone I and IIA, cyrtotanshinone, dihydrotanshinone I, carnosic acid, carnosol, and danshensu sodium salt were investigated against acetylcholinesterase, butyrylcholinesterase, urease and tyrosinase enzymes both in-vitro and in slico in detail. Elevated inhibitory effects on acetyl-and butyryl-cholinesterase of dihydrotanshinone I (IC50: 1.50 +/- 0.02 and 0.50 +/- 0.01 mu g/mL, respectively), carnasol (IC50: 11.15 +/- 0.05 ve 3.92 +/- 0.03 mu g/mL) and carnosic acid (IC50: 31.83 +/- 0.65 ve 4.12 +/- 0.04 mu g/mL) were observed. Furthermore, all other secondary metabolites were active against butyrylcholinesterase. Anti-urease (42.41 +/- 0.85%) and anti-tyrosinase (39.82 +/- 1.16%) activities of tanshinone I were also observed. Potential inhibitory effects of these molecules on target proteins were investigated using DOCK and molecular dynamics calculations. Dock score analysis and Lipinski parameters were demonstrated that these ligands are potential inhibitors against relevant enzymes. Our findings suggest that Salvia species can be utilized as a ptential source of anti-alzheimer active compounds for designing novel products.
Keywords: Nutrition; Salvia; Enzyme inhibition; Molecular Docking